Hubungan Intensitas Belajar dengan Hasil Belajar Matematika Siswa - Mufidah Mufidah; Akina Akina; Khairunnisa Khairunnisa; Nuraini Nuraini; Idris Idris (Jurnal Kreatif Online, 2021)
The purpose of this study was to determine the relationship between learning intensity and mathematics learning outcomes of students at SD Inpres 1 Donggulu. The method used in this research was experimental research, this type of research was a quantitative research that was correlated to fifth grade elementary school students, the sample in this study was 16 students. The research data were obtained in two ways; distributing questionnaires containing a number of statements to which the respondent's students responded, and obtaining midterm test scores on Mathematics from students who had been designated as respondents. The data obtained were analyzed quantitatively using the help of Statistical Package for the Social Sciences (SPSS) software version 23 for windows. The results of data analysis shown that the significance value (0.002) ≥ 0.05. It indicated that there was a relationship between learning intensity and student learning outcomes with the degree of strong correlation was 0.717.